2013
DOI: 10.1002/2013gl057963
|View full text |Cite
|
Sign up to set email alerts
|

Concentric waves and short‐period oscillations observed in the ionosphere after the 2013 Moore EF5 tornado

Abstract: [1] We detected clear concentric waves and short-period oscillations in the ionosphere after an Enhanced Fujita scale (EF)5 tornado hit Moore, Oklahoma, U.S., on 20 May 2013 using dense wide-coverage ionospheric total electron content (TEC) observations in North America. These concentric waves were nondispersive, with a horizontal wavelength of~120 km and a period of~13 min. They were observed for more than 7 h throughout North America. TEC oscillations with a period of 4 min were also observed to the south of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
176
2

Year Published

2014
2014
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 160 publications
(187 citation statements)
references
References 33 publications
9
176
2
Order By: Relevance
“…Waves above the Brunt-Väisälä frequency (>3.3 mHz, periods <5 min) have also been detected in mesospheric airglow spectral data [Pilger et al, 2013a[Pilger et al, , 2013b, consistent with acoustic or evanescent waves near the acoustic cutoff frequency; remote sensing of the D region likewise reveals short acoustic and gravity wave periods [Lay and Shao, 2011;Marshall and Snively, 2014]. Recent GPS observations of ionospheric TEC following the Moore, Oklahoma EF5 tornado-producing storm revealed ∼4 min periodicities southward of the storm center [Nishioka et al, 2013], illustrating clearly the direct spatial and temporal connections between tropospheric weather and localized periodic disturbances of the F region ionosphere. GPS network observations of natural hazard-related TEC perturbations reveal unprecedented detail into the spatial structure of wave fields and responses and have indicated that observed signatures are more pronounced in the magnetic equatorward direction from the source.…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…Waves above the Brunt-Väisälä frequency (>3.3 mHz, periods <5 min) have also been detected in mesospheric airglow spectral data [Pilger et al, 2013a[Pilger et al, , 2013b, consistent with acoustic or evanescent waves near the acoustic cutoff frequency; remote sensing of the D region likewise reveals short acoustic and gravity wave periods [Lay and Shao, 2011;Marshall and Snively, 2014]. Recent GPS observations of ionospheric TEC following the Moore, Oklahoma EF5 tornado-producing storm revealed ∼4 min periodicities southward of the storm center [Nishioka et al, 2013], illustrating clearly the direct spatial and temporal connections between tropospheric weather and localized periodic disturbances of the F region ionosphere. GPS network observations of natural hazard-related TEC perturbations reveal unprecedented detail into the spatial structure of wave fields and responses and have indicated that observed signatures are more pronounced in the magnetic equatorward direction from the source.…”
Section: Introductionmentioning
confidence: 86%
“…GPS network observations of natural hazard-related TEC perturbations reveal unprecedented detail into the spatial structure of wave fields and responses and have indicated that observed signatures are more pronounced in the magnetic equatorward direction from the source. This feature has been present in connection with a wide range of physical sources including, for example, volcanoes [Heki, 2006], weather events [Nishioka et al, 2013], earthquakes [Heki and Ping, 2005;Saito et al, 2011], and even rocket launches [Ding et al, 2014]. It has been proposed that this feature of the TEC perturbations is related to the local magnetic field geometry [Heki and Ping, 2005;Shinagawa et al, 2007].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other sources may be significant contributors to midlatitude MSTIDs. Tropospheric sources, such as convective overshoot from hurricanes [Vadas, 2007] and large convective systems [Nishioka et al, 2013], as well as AGWs launched by the solar terminator [Kotake et al, 2007], have all been linked to midlatitude MSTID observations. Midlatitude MSTIDs are ubiquitous, routinely observed, and have been shown to propagate over long distances.…”
Section: 1002/2014ja019870mentioning
confidence: 99%
“…After volcanic eruption (e.g., Heki 2006;Dautermann et al 2009) or massive tornado (e.g., Nishioka et al 2013), disturbances in total electron content (TEC) have been observed. After great earthquakes, short-period magnetic and atmospheric pressure oscillations (e.g., Iyemori et al 2005Iyemori et al , 2013 or TEC variations (e.g., Otsuka et al 2006;Saito et al 2011) were observed.…”
Section: Introductionmentioning
confidence: 99%